Hilal Observation using LRGB Filters - Firdaus, Muhammad Dimas; Putraga, Hariyadi; Ritonga, Marataon; Rakhmadi, Arwin Juli (Universitas Islam Negeri Mataram, 2024)
The technology used in hilal observation continues to develop. Most recently, using filters has become one of the options in hilal observation. Several filters can be used, ranging from low wavelengths like ultraviolet to high wavelengths like infrared. In some ideas, there needs to be a limit to the use of filters, the human eye's ability as a benchmark for the filter used. The human eye is sensitive to light with visual wavelengths, and one type of filter in this range is the LRGB filter. In this study, hilal observations were made on four filters and compared to find out which filter is better at increasing the contrast of hilal against the background. Using Michelson and Weber contrast as the definition of contrast to determine the comparison of the brightness value of the object with the background. From the observations made, it is found that the R filter will produce higher contrast values at low altitudes, followed by the L, G, and B filters. However, at higher altitudes, the contrast values of the L and R filters are similar, while the G and B filters remain low.